Return to sports activity following combined reconstructionof anterior cruciate ligament and anterolateral ligament - Štefanija Kolačko; Goran Vrgoč; Jurica Predović; Tomislav Kottek; Monika Trčak (Journal of Health Sciences)
Introduction: Anterior cruciate ligament (ACL) injuries are increasingly common among young people, especially active athletes. This study aims to retrospectively assess long-term results following ACL and anterolateral ligament (ALL) reconstruction, with a focus on rehabilitation, return to sports activities, patient satisfaction, and the impact of ALL and ACL injury on the s’ daily life and sports activities.